2012
DOI: 10.1172/jci61788
|View full text |Cite
|
Sign up to set email alerts
|

Defective B cell tolerance in adenosine deaminase deficiency is corrected by gene therapy

Abstract: Adenosine deaminase (ADA) gene defects are among the most common causes of SCID. Restoration of purine metabolism and immune functions can be achieved by enzyme replacement therapy, or more effectively by bone marrow transplant or HSC gene therapy (HSC-GT). However, autoimmune complications and autoantibody production, including anti-nuclear antibodies (ANAs), frequently occur in ADA-SCID patients after treatment. To assess whether ADA deficiency affects the establishment of B cell tolerance, we tested the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 49 publications
7
70
0
Order By: Relevance
“…We could show that WBD is capable not only of confirming the previously described hematopoietic alterations occurring in these individuals 4, 5, 6, 7, 9, 10, 17 but also of providing novel information on the hematopoietic landscape of these diseases. Indeed, together with the known defects in B cell contribution (Fig.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We could show that WBD is capable not only of confirming the previously described hematopoietic alterations occurring in these individuals 4, 5, 6, 7, 9, 10, 17 but also of providing novel information on the hematopoietic landscape of these diseases. Indeed, together with the known defects in B cell contribution (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…In particular, through WBD, in pediatric ADA‐SCID patients we could observe abnormal population frequencies in line with the characteristic block in B cell maturation. These patients displayed a higher content of immature B cells with respect to age‐matched HD 5 (79.5% vs. 53.9% of PreB cells in ADA‐SCID and Ped HD respectively. P  < 0.05 Mann‐Whitney test; Fig.…”
Section: Resultsmentioning
confidence: 93%
“…In previous studies, hBMSC-mediated immune suppression of activated B cells has been attributed to the secretion of antiproliferative soluble factors, such as PGE2, CCL2, CCL7, Blimp-1, and PD-1 and its ligands, as well as cell-to-cell contact [38][39][40][41][42], albeit not unanimously [34], and CD73, which is expressed in BMSCs, produces adenosine which can directly inhibit B cells [43,44]. In this study, we demonstrated that hPDLSCs suppressed B-cell proliferation through PD-1 and PD-L1 interaction in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, B cells with two TACI mutations were nearly unresponsive to such stimulation as also evidenced by the defective induction of the coactivation molecule ICOSL (Figure 2A and Supplemental Figure 1A). Similarly to adenosine deaminase (ADA) inhibition (25), TACI mutations imposed selective, not global, TLR7-and TLR9-dependent B cell activation defects because the induction of CD25 by TLR agonists was unaffected in B cells carrying TACI mutations ( Figure 2B and Supplemental Figure 1B). In addition, B cells with TACI mutations did not suffer from an intrinsic inability to upregulate CD86 because this molecule was normally induced after CD40 triggering ( Figure 2A).…”
Section: Central B Cell Tolerance Is Defective In All Subjects With Tmentioning
confidence: 99%
“…The first checkpoint occurs centrally in the bone marrow and is dependent upon B cell intrinsic factors including the BCR and TLR signaling pathways that mediate binding to self-antigens (22)(23)(24)(25). In contrast, regulation of the peripheral B cell tolerance checkpoint involves Tregs and potentially plasma BAFF concentrations (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%